Music for Older Adults: University Volunteer Programme for Social Improvement - Susana Sarfson; Mª Claudia Albini (Universidad Autónoma de Madrid, 2017)
This article presents a work carried out in Argentina for two years as the result of a public, competitive call for proposals. It was designed jointly by professors from the Universidad Nacional de las Artes (Argentina) and the Universidad de Zaragoza (Spain). The aims were: a) to offer quality musical activities to older adults, and b) to provide university students with the opportunity of participating in concrete actions on social improvement. The influence of this programme has been assessed on both aspects. Within a research-action framework, a programme of activities was designed jointly by university professors and students; a qualitative approach was chosen. Within a general aim to improve older adults' life quality, some specific differentiated objectives were developed, according to each group. The activities were performed by students from the faculty of Music (piano, singing, strings). Some initial, in-process and final evaluations were carried out. University students have contributed to a substantial improvement of older adults' life quality through musical activities adapted to each aged group (whether the independent, active community or the dependent one). They have also become aware of their potentiality to contribute to social betterness. This programme has been innovative and has promoted both independent and dependent older adults' well-being; it has also allowed university students of Music become engaged in societal needs and actively participate in social enhancement.